2010
DOI: 10.1111/j.1439-0426.2010.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of the silky shark Carcharhinus falciformis (Müller & Henle, 1839) off the western coast of Baja California Sur, Mexico

Abstract: Summary The objective of this study was to establish the trophic niche of the silky shark and to determine the ecological role of this predator in the ecosystem close to Baja California. The trophic spectrum was analyzed from samples taken during summer and autumn (2000–2002) from the fishing camps of Punta Lobos and Punta Belcher on the western coast of Baja California Sur. A total of 263 stomach contents were analyzed (143 with food; 120 empty). The index of relative importance (IRI) showed that at Punta Lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 15 publications
4
45
1
13
Order By: Relevance
“…The silky shark, Carcharhinus falciformis, feeds mainly on teleosts but also on cephalopods and crustaceans (Cabrera-Chávez et al 2010, Duffy et al 2015, Estupiñán-Montaño et al 2017) and, occasionally, on sea turtles (Estupiñán-Montaño et al 2017, Acevedo unpublished * ). This species is considered to be a selective predator in the ETP, with a preference for the scombrid genus Thunnus (see Duffy et al 2015, Estupiñán-Montaño et al 2017, which normally inhabits oceanic zones and forms schools near seamounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The silky shark, Carcharhinus falciformis, feeds mainly on teleosts but also on cephalopods and crustaceans (Cabrera-Chávez et al 2010, Duffy et al 2015, Estupiñán-Montaño et al 2017) and, occasionally, on sea turtles (Estupiñán-Montaño et al 2017, Acevedo unpublished * ). This species is considered to be a selective predator in the ETP, with a preference for the scombrid genus Thunnus (see Duffy et al 2015, Estupiñán-Montaño et al 2017, which normally inhabits oceanic zones and forms schools near seamounts.…”
Section: Discussionmentioning
confidence: 99%
“…Carcharhinus falciformis feeds on a large number of prey species, from pelagic and coastal fishes (e.g., tunas, mullets, mackerel) to cephalopods, crustaceans, and sea turtles (Cabrera-Chávez-Costa et al 2010, Duffy et al 2015, Estupiñán-Montaño et al 2017). This shark is considered a piscivorous predator, consuming mainly fishes of the Scombridae family (Duffy et al 2015, Estupiñán-Montaño et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…However, the individuals we sampled were significantly larger than those analysed by Rabehagasoa et al (2012). Therefore, ontogenetic shifts in diets, which have been documented for this species (Compagno 1984, Cabrera-Chávez-Costa et al 2010, Rabehagasoa et al 2012, may also explain the observed differences with C. falciformis feeding on higher trophic level prey at larger sizes. Moreover, higher δ…”
mentioning
confidence: 85%
“…Sehingga dapat diasumsikan bahwa hiu kejen menyeleksi jenis mangsa dan memakan mangsa dengan kelimpahan tinggi di perairan. Hal tersebut didukung oleh penelitian serupa yang dilakukan oleh Cabrera-Chaves- Costa et al 2010;Torres-Rojas et al 2009;Kamura et al 2004. Maka dapat diketahui pola makan ikan predator seperti hiu sangat kompleks dan dipengaruhi oleh berbagai macam faktor seperti ketersediaan makanan dan mobilitas mangsa, kelimpahan mangsa, ukuran mangsa, dan perubahan musim.…”
Section: Isi Lambung Hiu Kejen (Carcharhinus Falciformis)unclassified